Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Konsumen: Survey Pada Salah Satu Perusahaan Sepeda di Kota Bandung - Yudi Pratama; Imam Heryanto; Ashila Dwiyanisa; Imelda Megawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study examines the importance of service quality and product quality on consumer satisfaction. The survey was conducted on 150 customers at a bicycle retail company in the city of Bandung. This research uses path analysis technique to determine the effect of quality of service and product quality on consumer satisfaction, either partially or simultaneously. The results showed that service quality had the most substantial influence on consumer satisfaction, with the value of the importance of the effect being 32.5%. Product Quality has the second most substantial influence on Consumer Satisfaction, with a value of 24.9%. The results of the calculation of the coefficient of determination (R2) expressed in percentages describe the contribution of all independent variables, namely Service Quality (X1) and Product Quality (X2) in determining Customer Satisfaction (Y) of 57.4% and the amount of epsilon is = 0.426 or of 42.6% influenced by other factors not examined in this study.